Pengembangan Sistem E-Business untuk Cetak Dokumen Kapan Saja dan Dimana Saja Secara Online dengan Aplikasi Piranti Bergerak - Ziya El Arief; Adam Hendra Brata; Ratih Kartika Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The university student often receive assignments that need to be printed such as essay, reports, thesis, etc so that the document printing activity is neccessary for them. Outside printing activity feels very disturbing students' productivity because with that they must to walk to printing services, queue and be busy to find open printing services. In this research writer tries to solve the above issues with making a web-to-print e-business system. In this system customers just need to upload and choose the store where they want to take the document and after the document done he will receive notification and can take his document. The research done from requirement analysis stage, designing, implementation until testing stage. Program code implementation done by utilizing Ionic framework and PHP Codeigniter. The result of qualitative testing shows that the system is 100% validated which the testing is using basis path testing for white box testing and functional testing for black box testing. While quantitative testing result shows that the mobile application for customer can only run smoothly in Android KitKat devices or newer with internet connection HSPA+ or faster.